Meniscal Regenerative Scaffolds Based on Biopolymers and Polymers: Recent Status and Applications - Li, Hao; Li, Pinxue; Yang, Zhen; Gao, Cangjian; Fu, Liwei; Liao, Zhiyao; Zhao, Tianyuan; Cao, Fuyang; Chen, Wei; Peng, Yu; Yuan, Zhiguo; Sui, Xiang; et al. (Frontiers in Cell and Developmental Biology, 2021)
Knee menisci are structurally complex components that preserve appropriate biomechanics of the knee. Meniscal tissue is susceptible to injury and cannot heal spontaneously from most pathologies, especially considering the limited regenerative capacity of the inner avascular region. Conventional clinical treatments span from conservative therapy to meniscus implantation, all with limitations. There have been advances in meniscal tissue engineering and regenerative medicine in terms of potential combinations of polymeric biomaterials, endogenous cells and stimuli, resulting in innovative strategies. Recently, polymeric scaffolds have provided researchers with a powerful instrument to rationally support the requirements for meniscal tissue regeneration, ranging from an ideal architecture to biocompatibility and bioactivity. However, multiple challenges involving the anisotropic structure, sophisticated regenerative process, and challenging healing environment of the meniscus still create barriers to clinical application. Advances in scaffold manufacturing technology, temporal regulation of molecular signaling and investigation of host immunoresponses to scaffolds in tissue engineering provide alternative strategies, and studies have shed light on this field. Accordingly, this review aims to summarize the current polymers used to fabricate meniscal scaffolds and their applications in vivo and in vitro to evaluate their potential utility in meniscal tissue engineering. Recent progress on combinations of two or more types of polymers is described, with a focus on advanced strategies associated with technologies and immune compatibility and tunability. Finally, we discuss the current challenges and future prospects for regenerating injured meniscal tissues.